Patient Information About Zika Virus and Perinatal Risks on State Health Department Websites in the United States [17I]. Issue 1 (May 2017) - Menchaca, Ryan; Page-Ramsey, Sarah M.; Rodriguez, Emma; Gray, Jordan; Ireland, Kayla; Ramsey, Patrick S.
Abstract : INTRODUCTION: Zika virus infection is an emerging health threat in pregnant women. It is important that obstetric patients or women considering pregnancy can access up-to-date information about Zika. Our objective was to evaluate the availability of patient-level information about the Zika virus and perinatal risks on state health department websites in the United States and its territories. METHODS: We reviewed each U.S. state, District of Columbia and its territories (Puerto Rico, Guam, US Virgin Islands, American Samoa, North Marianas Islands) health department websites and abstracted patient information available on the Zika virus, pregnancy risks, prevention measures, mosquito repellants, sexual transmission, endemic areas, and travel guidance. In cases where information did not appear immediately on the main webpage, an internal search of the site using the term "Zika" was performed. RESULTS: 96.4% of the 56 state/territory health department websites contained patient information about Zika virus. Information was more commonly found on state websites than on territories websites (98.0% vs 60.0%). Among the state/territory websites with any Zika information, specific information noted details about the Zika virus (98.1%), pregnancy risks (84.6%), risk of microcephaly (76.9%), sexual transmission (82.7%), mosquito repellant use (71.2%), travel avoidance (84.6%), and Zika endemic areas (90.1%). CONCLUSION: Patient access to Zika virus information is available on most US state and territory health department websites, though less common on territory sites. Because patients need to easily access educational information about Zika virus infection in pregnancy, we should aim to have this information available on all state and territory sites.